2007
DOI: 10.4269/ajtmh.2007.76.144
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses in Human Dendritic Cells Upon Infection by Chimeric Yellow-Fever Dengue Vaccine Serotypes 1–4

Abstract: Dengue infection is an important public health issue worldwide. The ChimeriVax-Dengue (CYD) vaccine uses yellow fever (YF) 17D vaccine as a live vector. Dendritic cells (DCs) play a key role in initiating immune responses and could be an important primary target of dengue infection. We investigated in vitro the consequences of CYD infection of DCs on their activation/maturation and cytokine production. In CYD-infected DCs, we observed an up-regulation of HLA-DR, CD80, CD86, and CD83. Cells exposed to CYD secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
4
30
1
Order By: Relevance
“…The YF17DD vaccine virus infects cells at inoculum doses equivalent to those used for DENV2 (16681 strain) but showed reduced expression of viral antigens within DCs at all time points tested when compared to DENV. Similar results were described for the YF vaccine strain 204, which is poorly infectious compared with DENV (Deauvieau et al 2007). Other authors used higher MOIs for DENV to obtain the same relative infection level as West Nile virus because these viruses replicate at different rates.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The YF17DD vaccine virus infects cells at inoculum doses equivalent to those used for DENV2 (16681 strain) but showed reduced expression of viral antigens within DCs at all time points tested when compared to DENV. Similar results were described for the YF vaccine strain 204, which is poorly infectious compared with DENV (Deauvieau et al 2007). Other authors used higher MOIs for DENV to obtain the same relative infection level as West Nile virus because these viruses replicate at different rates.…”
Section: Discussionsupporting
confidence: 73%
“…In our in vitro infection model, we observed markedly higher TNF-α production after infection with pathogenic virus (DENV2) as compared to the non-pathogenic viruses (YF17DD and YF17D/DENV2), providing further evidence that this cytokine plays a role in flavivirus immunopathogenesis. Other authors have also observed TNF-α production in DC or monocyte cultures in the presence of DENV2 and some authors even associate it with the infected cell (Hacker et al 1998, Querec et al 2006, Deauvieau et al 2007, Reis et al 2007, Ahmad et al 2008, Nightingale et al 2008, Levy et al 2009. A moderate level of TNF-α production may be beneficial to mature cells that may become good antigen presenters.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations